1991
DOI: 10.1007/bf01644948
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental immunoglobulin (ivIgG) treatment in 163 patients with sepsis and septic shock — An observational study as a prerequisite for placebo-controlled clinical trials

Abstract: In a multicenter observational study of 163 medical and surgical patients with a total of 173 episodes of sepsis or septic shock (Elebute sepsis score: 19.0 +/- 0.5), the effects of supplemental i.v. immunoglobulin (i.v. IG) treatment (unmodified polyvalent IgG pH 4.25, n = 123; for Pseudomonas sepsis, n = 50, Pseudomonas IgG) on multiple organ failure (MOF) were investigated by means of APACHE II score changes (pretreatment: 23.7 +/- 0.6). In 44% of the cases ("responders"), a prompt improvement in APACHE II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Indeed, Rivers et al (30) found a slight but significant difference in serial APACHE II scores (3 points) to be associated with a 16% difference in mortality when comparing early goal-directed therapy with standard therapy in patients with sepsis. The specific 4-point reduction used in our study has also been shown to predict improvements in 28-day mortality rate in previous sepsis studies (23,24). The SOFA score was also calculated, since changes in this score also relate to mortality rate and SOFA provides discrimination between specific organ systems.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Indeed, Rivers et al (30) found a slight but significant difference in serial APACHE II scores (3 points) to be associated with a 16% difference in mortality when comparing early goal-directed therapy with standard therapy in patients with sepsis. The specific 4-point reduction used in our study has also been shown to predict improvements in 28-day mortality rate in previous sepsis studies (23,24). The SOFA score was also calculated, since changes in this score also relate to mortality rate and SOFA provides discrimination between specific organ systems.…”
Section: Discussionmentioning
confidence: 79%
“…We have therefore performed an initial multiple-center phase II study of the safety and therapeutic effect of this adsorption treatment in presumed Gram-negative sepsis. A reduction in the Acute Physiology And Chronic Health Evaluation (APACHE) II score of Ն4 points over the first 4 days was chosen as primary end point, since this has been shown to predict improved 28-day mortality rate in studies of immunoglobulin therapy in septic patients (23,24).…”
Section: Ndotoxin (Lipopolysaccharide)mentioning
confidence: 99%
“…In an observational study, where 163 septic patients were treated with lgG-IVIG, likewise no increase in serum creatinine was observed within the first four days after receiving PolyglobinR Nand PsomaglobinR N (Bayer AG, Leverkusen, Germany) on day 0 and day I, repectively. Serum creatinine (mean values) on day 0 were 2·4-2·5mg/100ml and on day 4, 2·2-2·3mg/IOOml [24]. For viral safety of IVIG, see Yap, this supplement, pp 35-42.…”
Section: Dosage Regimens Ac!tiel'(fble Serum Immunoglobulin Levels Amentioning
confidence: 99%
“…The protocol of the SBITS study has been published [14), and the results will be available by the end of 1996. The estimations of the expected mortality in the placebo group and the reduction of mortality in the treatment group rely on the data from a preceding observational study [24) and reflect the selection of patient subgroups included. in contrast to the qualitative sepsis criteria usually applied, the SBITS study, for the first time, uses quantitative score inclusion criteria regarding assessment of sepsis and disease severity, the sector with potentially maximal benefit as previously validated [24).…”
Section: Therapeutic Option: Reduction In Mortality In 'The Total Popmentioning
confidence: 99%
See 1 more Smart Citation